2016
DOI: 10.1128/mbio.00655-16
|View full text |Cite
|
Sign up to set email alerts
|

Heteroresistance to Fluconazole Is a Continuously Distributed Phenotype among Candida glabrata Clinical Strains Associated with In Vivo Persistence

Abstract: Candida glabrata causes persistent infections in patients treated with fluconazole and often acquires resistance following exposure to the drug. Here we found that clinical strains of C. glabrata exhibit cell-to-cell variation in drug response (heteroresistance). We used population analysis profiling (PAP) to assess fluconazole heteroresistance (FLCHR) and to ask if it is a binary trait or a continuous phenotype. Thirty (57.6%) of 52 fluconazole-sensitive clinical C. glabrata isolates met accepted dichotomous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 36 publications
1
69
0
Order By: Relevance
“…As stated earlier, specific pdr1 mutations can also enhance the fitness of C. glabrata and increase virulence through adhesion upregulation (Vale-Silva et al, 2016). C. glabrata heteroresistance was not observed in response to the echinocandins, which may reflect its fungicidal mechanism of action (at least in vitro ) (Ben-Ami et al, 2016) or potential associated fitness costs. However, yeast are exposed to additional pressures in vivo that may induce some kind of transient heterotolerance to the echinocandins that is not necessarily measurable in vitro .…”
Section: The Adaptive Responsementioning
confidence: 97%
See 1 more Smart Citation
“…As stated earlier, specific pdr1 mutations can also enhance the fitness of C. glabrata and increase virulence through adhesion upregulation (Vale-Silva et al, 2016). C. glabrata heteroresistance was not observed in response to the echinocandins, which may reflect its fungicidal mechanism of action (at least in vitro ) (Ben-Ami et al, 2016) or potential associated fitness costs. However, yeast are exposed to additional pressures in vivo that may induce some kind of transient heterotolerance to the echinocandins that is not necessarily measurable in vitro .…”
Section: The Adaptive Responsementioning
confidence: 97%
“…Although acquisition of a pdr1 mutation is required for stable triazole resistance, studies have demonstrated the ability of C. glabrata subpopulations originating from a clonal population to develop heteroresistance to fluconazole through transient upregulation of efflux pumps (Claudino et al, 2009; Ben-Ami et al, 2016). Development of tolerance to fluconazole treatment at the population level may be one consequence of heteroresistance, which in turn, may allow the yeast to adapt and “buy time” until beneficial, stable mutations develop.…”
Section: The Adaptive Responsementioning
confidence: 99%
“…In vitro studies have shown that the adhesion of non-albicans species to buccal epithelial and vascular endothelial cells is weaker than that of C. albicans (26). C. glabrata, which is the second most frequently isolated fungus causing single infections or combined infections with C. albicans, causes persistent infections in patients treated with fluconazole and often acquires resistance to antifungal drugs (27). Because the sensitivity to antifungal drugs varies, identification of Candida species is important for treatment of candidiasis, allowing physicians to prescribe the appropriate antifungal drug.…”
Section: Discussionmentioning
confidence: 99%
“…For fungi, some studies show that heteroresistance to azoles seems to be intrinsic and others indicate that it is acquired. Several studies focused on Cryptococcus heteroresistance showed that all strains tested in repeated exposure to fluconazole or itraconazole led to a subset of resistant subpopulations . However, different data were found for Candida glabrata, Aspergillus fumigatus and even for Cryptococcus neoformans (Table ).…”
Section: The Concept Of Heteroresistancementioning
confidence: 99%
“…Several studies focused on Cryptococcus heteroresistance showed that all strains tested in repeated exposure to fluconazole or itraconazole led to a subset of resistant subpopulations . However, different data were found for Candida glabrata, Aspergillus fumigatus and even for Cryptococcus neoformans (Table ). These difference in the results may be attributed to the subset of strains tested and also to the different methodologies used, demonstrating the need for well‐established standards to study heteroresistance.…”
Section: The Concept Of Heteroresistancementioning
confidence: 99%